Effect of Leader-Member Exchange on Job Performance Moderated by Employee’s Emotions and Employee’s Behavior on Banking Industries in Batam - Agustinus Setyawan; Yuki Milenia (Pascasarjana STIE Amkop Makassar, 2022)
AbstractBanking industries, if the role goes well, a country’s economy will improve. Banking is an industry which handles cash, credit and other financial transactions. So were human resources. Company goals or survival of the company, it all depends on the quality of the human resources in there. A leader, other than being able to lead their subordinates, a leader also must be able to empathize too. The aims of this research were to study how Leader-Member Exchange (LMX) will affect Employee’s Job Performance on Banking Industries by using SmartPLS 3.0. Of course, it moderate by Employee’s Emotions and Behavior. Emotions will affect someone performance from doing their task. How the result turns out, it depends on their mood and behavior at that time. Data were collected by spreading questionnaire to those who works on Banking Industries in Batam. Author received 143 respondents in back. Result show significancy and insignificancy between variables. Leader-Member Exchange indirectly affected Job Performance. Keywords: Leader-Member Exchange, Job Performance, Banking Industries.